The Factors Affecting the Increase in Local Revenue of the City of Medan - Sangkot Khadijah; Agus Tripriyono (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the factors influencing the increase in Local Revenue of the City of Medan, focusing on Gross Regional Domestic Product (GRDP) and population size as the main variables. Using a quantitative approach with multiple linear regression analysis, this study analyzes secondary data from the period 2001–2024 obtained from the Central Statistics Agency (BPS). The results indicate that GRDP has a positive and significant effect on the City of Medan’s local revenue. Every increase in RDP is proportional to an increase in local revenue, indicating that regional economic growth directly drives the region’s capacity to generate more revenue from taxes and fees. Similarly, population size demonstrates a positive influence on local revenue, reflecting that an increase in population expands the tax and fee base, thereby enhancing the region’s revenue potential. Simultaneously, GRDP and population together explain approximately 92.9% of the variation in local revenue in the City of Medan, indicating the significant contribution of these two variables in determining local fiscal performance. This finding aligns with the Theory of Fiscal Decentralization, which states that regions capable of effectively managing economic and demographic factors will be better positioned to achieve fiscal autonomy. Based on these findings, it is recommended that the Medan City Government optimize economic sectors that can accelerate GRDP growth and leverage the city’s population to increase sustainable local revenue through more effective fiscal policies.